Caracterização geológica e geofísica do Aquifero Pantanal, região de Poconé – MT - Lopes, Annika Ferreira (2018)
The Pantanal, located in the center-west of Brazil is the largest wetland in the world, this region is considered by UNESCO as World Natural Heritage and Biosphere Reserve. The portion of this patrimony reported here is located in the southern region of the state of Mato Grosso, more precisely in the region of the municipality of Poconé, entitled "the gateway of the Matogrossense Pantanal". The Pantanal Basin is a product of tectonics in the region in response to Andean Orogeny, and the sediments that the basin receives are deposited directly on the pre-Cambrian rocks of the Paraguayan Range. In this work the objective is to increase the knowledge about neotectonics at the edge of the basin and also to increase knowledge about the sediments that host the Pantanal Aquifer. For this purpose, the interpretation of photollectors was carried out to characterize the main structures that can accommodate basin subsidence, associated with geophysical survey, with the technique of Vertical Electrical Survey to characterize the physical properties of the sediments of the Basin and thus generate information about thickness, depth and composition of the different existing sedimentary layers, making possible to infer its subsurface structure. The results generated a geological model for the worked session, which show that the basin's basement is in constant subsidence, accommodated in normal faults found between Poles 2 and 3, 3 and 4 and also between poles 4 and 5, showing that the basin is in constant transformation and receiving sediment deposition. The Pantanal Formation was shown to be a thick sediment packet with clay and sandy intercalations, reaching 611 meters thick in some places, showing suitable sites to host the aquifer.